Diode Dosimetric Characterisations And Assessments For In-Vivo Dosimetry In Radiotherapy Treatment - Marzuki, Rahmatfadli (2019)
Diode is a kind of radiation dosimetry system that has been applied widely in radiotherapy treatment and very useful for in-vivo dosimetry (IVD). It is duly important to understand the characteristic of detector before it can be used in clinical treatment. In this study, characteristics of three (3) diodes IBA EDP-153G model were analyzed and compared to calibrated ionization chamber. The 6 MV linear accelerator (Linac) was used with different field sizes (FS), source to surface distance (SSD), linac monitor unit (MU), tray field (TF) wedge field (WF) and diode reading behind cerroband. Actual diode thickness, diode reproducibility, perturbation effect and diode effect with radiation beam angle and temperature were performed. From the determination of diode dosimetric characteristic, a clinical computerized treatment planning system (TPS) model Elekta Monaco and calibrated ionization chamber were used to verify the accuracy of diode reading in different treatment techniques. In this study, EDP-153G diode was sensitive with angle of incidence, wedge, SSD and temperature. The measured angle for diode were less than 2 % at angle ± 41°, ± 37° and ± 72° for diode 1, diode 2 and diode 3 respectively. SSD correction factors have increased proportionally by increasing the SSD. SSD correction factor from SSD 75 cm to 140 cm 0.995 to 1.025, 0.975 to 1.046 and 0.989 to 1.021 for diode 1, diode 2 and diode 3 respectively. Wedge correction factors have increased proportionally by increasing the wedge angle Diode wedge correction factor resulted in the range of 1.003 to 1.023, 1.009 to 1.033 and 1.011 to 1.056 for diode 1, diode 2 and diode 3 respectively.